An environmental barrier coating for c / c composites and a method for producing the same
Patent Information
- Application Number
- CN202410185021.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-19
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-02-19
AI Technical Summary
[0004]本发明的目的在于克服上述现有技术的缺点,提供一种用于C/C复合材料的环境障涂层及其制备方法,以解决现有技术中Yb2Si2O7涂层易于被腐蚀,如果加入Yb2SiO5易使涂层中产生垂直贯穿裂纹的问题
[0024]本发明涉及一种用于C/C复合材料的环境障涂层的制备方法,该方法首先利用熔盐工艺,将Yb2Si2O7粉、Al粉与充分干燥后的NaCl粉、KCl粉按一定比例混合均匀,并进行高温热处理,制得具有核壳结构的Yb2Si2O7@Al2O3复合喷涂粉体;随后采用热喷涂工艺在包埋有粘结层SiC的C/C复合材料表面沉积Yb2Si2O7-Al2O3陶瓷面层。上述制备方法可实现Yb2Si2O7涂层中微纳尺度Al2O3的均匀掺杂,并在涂层中原位反应生成具有高损伤容限及优异耐水汽腐蚀能力的Yb3Al5O12相,能有效增强C/C复合材料在高温水氧腐蚀环境中的热循环服役稳定性。
Smart Images

Figure CN118048597B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating technology, specifically relating to an environmental barrier coating for C / C composite materials and its preparation method. Background Technology
[0002] C / C composites have become ideal hot-end structural materials for aerospace engines due to their low density and excellent high-temperature mechanical properties. However, the severe oxidation above 500℃ greatly limits the practical application of C / C composites. Based on this, SiC-based composite coatings have been widely studied due to their matching coefficient of thermal expansion with C / C and good physicochemical compatibility. In high-temperature oxygen-containing environments, the dense SiO2 protective film formed on the surface of SiC-based composite coatings can effectively hinder the internal diffusion of oxygen. However, in engine environments containing water vapor, the SiO2 protective film will transform into gaseous Si(OH)4, thereby losing its protective performance (SLdos Santos eLucato, OH Sudre, DB Marshall, A method for assessing reactions of water vapor with materials in high-speed, high-temperature flow[J], Journal of the American Ceramic Society, 2011, 94(S1):S186-S195.). Therefore, it is crucial to prepare environmental barrier coatings (EBCs) with low SiO2 activity on the surface of silicon-based oxygen barrier coatings.
[0003] Taking into account high-temperature corrosion resistance, phase structure stability, and thermal expansion compatibility (Yb2Si2O7: 4.1×10), - 6 K -1 SiC: 4.3~5.4×10 -6 K -1Yb₂Si₂O₇ has become the preferred material for surface EBCs on SiC-based materials (M. Ridley, E. Opila, Thermochemical stability and microstructural evolution of Yb₂Si₂O₇ in high-velocity high-temperature water vapor[J], Journal of the European Ceramic Society, 2021, 41(5):3141-3149.). Existing research shows that introducing Yb₂SiO₅ into the interior or surface of Yb₂Si₂O₇ coatings can improve the coating's resistance to water vapor corrosion. Although Yb2SiO5 has a lower SiO2 activity, its higher coefficient of thermal expansion and lower fracture toughness compared to Yb2Si2O7 make it highly susceptible to vertical through-cracks in the coating (X.Wang, Z.Xue, Z.Zhou, E.Byon, S.Zhang, Influence of Yb2Si2O7 doping concentration on mechanical properties and thermal conductivity of Yb2SiO5-Yb2Si2O7 composite ceramics[J], Journal of Alloys and Compounds, 2022, 889:161718.). On the other hand, in a high-temperature water vapor corrosion environment, the formation of a porous Yb2SiO5 corrosion layer on the surface of Yb2Si2O7 limits its long-term stable service (X.Zhong,R.Liang,D.Hong,D.Fan,Y.Wu,L.Wang,Q.Li,Y.Niu,X.Zheng,Corrosion behavior and mechanismof ytterbium silicates environmental barrier coatings subjected to thermalcycling in water vapor[J],Journal of the American Ceramic Society,2023:1-17.). Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide an environmental barrier coating for C / C composite materials and its preparation method, so as to solve the problem that Yb2Si2O7 coatings are easily corroded and vertical through cracks are easily generated in the coating if Yb2SiO5 is added.
[0005] To achieve the above objectives, the present invention employs the following technical solution:
[0006] A method for preparing an environmental barrier coating for C / C composite materials includes the following steps:
[0007] Step 1: Mix Al powder, Yb2Si2O7 powder, NaCl powder and KCl powder, and grind them to obtain a mixed powder;
[0008] Step 2: Heat and hold the mixed powder in a heating furnace to obtain the heat-treated mixed powder;
[0009] Step 3: Perform ultrasonic cleaning on the heat-treated mixed powder several times, and dry the final ultrasonically cleaned slurry to obtain Yb2Si2O7@Al core-shell powder.
[0010] Step 4: Oxidize the Yb2Si2O7@Al core-shell powder to obtain Yb2Si2O7@Al2O3 core-shell powder;
[0011] Step 5: Deposit Yb2Si2O7-Al2O3 core-shell powder on the surface of the C / C composite material with embedded SiC binder layer to obtain Yb2Si2O7-Al2O3 ceramic surface layer;
[0012] Step 6: The C / C composite material with Yb2Si2O7-Al2O3 ceramic surface layer deposited on the surface is heat-treated in a heating furnace to obtain an environmental barrier coating for the C / C composite material.
[0013] A further improvement of the present invention is that:
[0014] Preferably, in step 1, the molar ratio of Al powder, Yb2Si2O7 powder, NaCl powder and KCl powder is (0.1~0.3):1:(0.3~0.7):(0.3~0.7).
[0015] Preferably, in step 1, the NaCl powder and KCl powder are dried.
[0016] Preferably, in step 2, the heat preservation temperature is 700-1000℃, the heat preservation environment is Ar atmosphere, and the heat preservation time is 4-6h.
[0017] Preferably, in step 3, the ultrasonic cleaning is performed 5 times, and the liquid temperature used in the ultrasonic cleaning is 80°C.
[0018] Preferably, in step 3, the slurry drying temperature is 100℃ and the drying time is 10h.
[0019] Preferably, in step 4, the oxidation temperature is 500℃ and the oxidation time is 4 to 6 hours.
[0020] Preferably, in step 5, Yb2Si2O7-Al2O3 core-shell powder is deposited by plasma spraying, with a spraying power of 45-50kW and a spraying distance of 80-120mm.
[0021] Preferably, in step 6, the heat preservation temperature is 1100-1300℃, the heat preservation atmosphere is Ar atmosphere, and the heat preservation time is 10-15h.
[0022] An environmental barrier coating for C / C composite materials obtained by any of the above preparation methods, wherein the environmental barrier coating comprises, from the inside out, a SiC bonding layer and a Yb2Si2O7-Al2O3 ceramic surface layer.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] This invention relates to a method for preparing an environmental barrier coating for C / C composite materials. The method first utilizes a molten salt process to uniformly mix Yb₂Si₂O₇ powder, Al powder, and thoroughly dried NaCl and KCl powders in a specific ratio, followed by high-temperature heat treatment to obtain a core-shell structured Yb₂Si₂O₇@Al₂O₃ composite sprayable powder. Subsequently, a Yb₂Si₂O₇-Al₂O₃ ceramic surface layer is deposited on the surface of the C / C composite material with an embedded SiC binder layer using a thermal spraying process. This preparation method achieves uniform doping of micro / nano-scale Al₂O₃ in the Yb₂Si₂O₇ coating and generates Yb₃Al₅O₃ with high damage tolerance and excellent resistance to water vapor corrosion in situ within the coating. 12 This phase can effectively enhance the thermal cycling stability of C / C composite materials in high-temperature water-oxygen corrosion environments.
[0025] Furthermore, this invention employs a high-temperature molten salt method combined with plasma spraying to achieve uniform doping of the micro-nano scale second phase in the coating. Utilizing the low eutectic melting point of NaCl-KCl (approximately 670℃), a sufficient liquid phase environment is provided for the mixed powder at temperatures above 670℃, ensuring the uniform diffusion of liquid Al to the surface of Yb₂Si₂O₇ particles. Finally, combined with pre-oxidation treatment, an Al₂O₇ shell with a thickness of less than 1 μm is coated onto the surface of the Yb₂Si₂O₇ sprayed powder, resulting in a Yb₂Si₂O₇@Al₂O₇ composite sprayed powder with a core-shell structure.
[0026] Furthermore, a Yb2Si2O7-Al2O3 ceramic surface layer was deposited on the C / C surface embedded with SiC using a plasma spraying process to obtain a micro-nano scale Al2O3 doped and optimized Yb2Si2O7 coating.
[0027] This invention also discloses an environmental barrier coating for C / C composite materials. The environmental barrier coating comprises, from the inside out, a SiC bonding layer and a Yb₂Si₂O₇-Al₂O₃ ceramic surface layer. During high-temperature service, the Yb₂Si₂O₇-Al₂O₃ ceramic surface layer undergoes an in-situ reaction to generate Yb₃Al₅O₃, which exhibits excellent corrosion resistance. 12 This phase improves the coating's resistance to high-temperature water vapor corrosion.
[0028] Under subsequent oxidizing service conditions, the in-situ reaction of Al2O3 in the coating enriches Yb3Al5O3 inside and on the surface of the coating, resulting in high damage tolerance and excellent resistance to water vapor corrosion. 12 Phase (Yb2Si2O7+5 / 3Al2O3→2 / 3Yb3Al5O) 12 The addition of SiO2 (+2SiO2) resulted in no porous corrosion layer appearing on the coating surface after 200 hours of water-oxygen corrosion at 1500℃. The SiO2 displaced in situ further transformed the low-toughness Yb2SiO5 generated during spraying into Yb2Si2O7 (Yb2SiO5+SiO2→Yb2Si2O7), enhancing the thermal cycling stability of the Yb2Si2O7 surface on the C / C composite material in a high-temperature water-oxygen corrosion environment. This reduced cracking caused by the introduction of Yb2SiO5 with its high thermal expansion coefficient and low fracture toughness. After 200 hours of water-oxygen corrosion at 1500℃, the Yb2Si2O7-Al2O3 coating sample gained approximately three times the weight of the pure Yb2Si2O7 coating sample, indicating the former's superior resistance to high-temperature water vapor corrosion.
[0029] Furthermore, uniformly doping the main phase (Yb2Si2O7) powder with micro-nano-scale Al2O3 second phase effectively avoids the residue of the spray decomposition product Yb2SiO5, which is of great significance for reducing the number of open-pore defects in the Yb2Si2O7 coating and improving the thermal cycling stability of the coating. It also provides a new approach for optimizing the performance of other rare earth bis-silicate environmental barrier coatings. Attached Figure Description
[0030] Figure 1 The following are cross-sectional backscattering morphology images and corresponding elemental analyses of the Yb2Si2O7@Al2O3 core-shell powder prepared in Example 3 of this invention:
[0031] (a) Cross-sectional backscattered image of Yb₂Si₂O₇@Al₂O₃ core-shell powder, (b) Surface scan distribution of corresponding elements, (c) Enlarged morphology of region 1 in Figure (a), (d) Line scan data of corresponding elements at the corresponding position in Figure (c). Based on the distribution of Al and O elements, it can be seen that the spherical Yb₂Si₂O₇ powder surface is successfully coated with an Al₂O₃ shell with a thickness of approximately 0.4 μm. Furthermore, the elemental scan data shows that the distributions of Al and Yb elements partially overlap, mainly due to the Al-K... α (1.48keV) and Yb-M α This is due to the overlap between the (1.51keV) energy lines.
[0032] Figure 2 The XRD patterns of the surfaces of the samples corresponding to Example 3 and Comparative Example 3 after oxidation in an environment of 1500℃, 50 vol.% O2 + 50 vol.% H2O for 200 h are shown.
[0033] Figure 3 The following is a cross-sectional backscattering morphology of the sample corresponding to Example 3 after oxidation in an environment of 1500℃, 50 vol.% O2 + 50 vol.% H2O for 200 h:
[0034] (a) Low magnification morphology of Yb2Si2O7-Al2O3 coated sample after water-oxygen corrosion, (b) Local magnified morphology of the reaction layer, (c) Local magnified morphology of the middle part of Yb2Si2O7-Al2O3 surface layer, (d) Local magnified morphology of thermally grown oxide (TGO) layer.
[0035] Figure 4 The backscattering morphology of the cross section of the sample corresponding to Comparative Example 3 after oxidation in an environment of 1500℃, 50 vol.% O2 + 50 vol.% H2O for 200 h is shown below:
[0036] (a) Low-magnification morphology of Yb2Si2O7 coated sample after water-oxygen corrosion; (d) Local magnified morphology of the reaction layer; (c) Local magnified morphology of the middle part of Yb2Si2O7 surface layer; (d) Local magnified morphology of thermally grown oxide layer.
[0037] Figure 5 The following data pertain to the mass changes and the thicknesses of the thermally grown oxide layer and reaction layer of the samples corresponding to Example 3 and Comparative Example 3 after oxidation at 1500°C in a 50 vol.% O2 + 50 vol.% H2O environment for 200 h:
[0038] (a) Mass change of Yb2Si2O7 and Yb2Si2O7-Al2O3 coated samples after 200 h of water and oxygen; (b) Statistical analysis of the thickness of thermally grown oxide layer and reaction layer of Yb2Si2O7 and Yb2Si2O7-Al2O3 coated samples after 200 h of water and oxygen; (c) Schematic diagram of coating structure. Detailed Implementation
[0039] The present invention will now be described in further detail with reference to the accompanying drawings:
[0040] This invention discloses a method for preparing an environmental barrier coating for C / C composite materials, the preparation steps of which are as follows:
[0041] Step 1: Weigh Al, Yb2Si2O7 powder and fully dried NaCl and KCl powder in a molar ratio of (0.1-0.3):1:(0.3-0.7):(0.3-0.7). Place the weighed powder in an alumina mortar and grind manually for 20 minutes to obtain a mixed powder.
[0042] Among them, Al and Yb2Si2O7 powders are spherical powders with particle sizes of 30-50 μm and 10-55 μm respectively; NaCl and KCl powders are of analytical grade; the fully dried NaCl and KCl powders are obtained by holding them in an Ar atmosphere at a high temperature of 200-250℃ for 4-6 hours to remove the crystal water in the powder.
[0043] In this step, the powder is thoroughly mixed through mixing and grinding.
[0044] Step 2: Place the mixed powder in a covered alumina crucible, put the crucible into a high-temperature tubular heat treatment furnace, and keep it at 700-1000℃ in an Ar atmosphere for 4-6 hours.
[0045] In this process, the low eutectic melting point of NaCl-KCl (around 670℃) is utilized to provide a sufficient liquid phase environment for the mixed powder at a temperature above 670℃, ensuring the uniformity of liquid Al diffusion to the surface of Yb2Si2O7 particles.
[0046] Step 3: Place the high-temperature treated mixed powder in deionized water and ultrasonically clean it at 80°C for 30 minutes to fully dissolve the molten salt. Then, let the mixed slurry stand, pour out the supernatant, repeat the ultrasonic cleaning ≥3 times and let it stand and pour out the supernatant to remove NaCl and KCl. Finally, place it in a 100°C oven for 10 hours to obtain fully dried Yb2Si2O7@Al core-shell powder.
[0047] Step 4: Place the Yb2Si2O7@Al core-shell powder in a high-temperature box furnace and oxidize it at 500°C in air for 4-6 hours to obtain Yb2Si2O7@Al2O3 core-shell powder for spraying.
[0048] The core-shell structure of Yb2Si2O7@Al2O3 powder enables uniform Al2O3 doping.
[0049] Step 5: Deposit a Yb2Si2O7-Al2O3 ceramic surface layer on the surface of the C / C composite material with embedded SiC bonding layer using plasma spraying process, wherein the spraying power is 45-50kW and the spraying distance is 80-120mm.
[0050] Step 6: Place the sample coated with Yb2Si2O7-Al2O3 ceramic surface layer in a high-temperature tubular heat treatment furnace and keep it at 1100-1300℃ in an Ar atmosphere for 10-15 hours.
[0051] This invention discloses an environmental barrier coating for C / C composite materials, wherein the environmental barrier coating comprises, from the inside out, a SiC bonding layer and a Yb2Si2O7-Al2O3 ceramic surface layer.
[0052] Example 1:
[0053] Step 1: Place NaCl and KCl powders separately in a high-temperature tube heat treatment furnace, raise the temperature to 250℃ at a heating rate of 5℃ / min under Ar atmosphere and hold for 4 hours, then let them cool naturally to room temperature to ensure that the NaCl and KCl powders are fully dried.
[0054] Step 2: Weigh Al and Yb2Si2O7 powder and NaCl and KCl powder obtained in Step 1 at a molar ratio of 0.2:1:0.6:0.6. Place the weighed powder in an alumina mortar and grind manually for 20 minutes to obtain a mixed powder.
[0055] Step 3: Place the mixed powder obtained in Step 2 in a high-temperature tube heat treatment furnace, heat it to 900℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 6 hours. Place the high-temperature treated mixed powder in deionized water and ultrasonically clean it at 80℃ for 30 minutes. Then, let the mixed slurry stand and pour off the supernatant. Repeat the above cleaning operation 5 times to remove NaCl and KCl. Place the completely cleaned mixed slurry in a 100℃ oven for 10 hours to obtain fully dried Yb2Si2O7@Al core-shell powder.
[0056] Step 4: Place the Yb2Si2O7@Al core-shell powder obtained in Step 3 into a high-temperature box furnace, raise the temperature to 500℃ at a heating rate of 5℃ / min in air atmosphere and hold for 6h to obtain Yb2Si2O7@Al2O3 core-shell powder for spraying.
[0057] Step 5: The Yb2Si2O7@Al2O3 core-shell powder obtained in Step 4 is loaded into a plasma spraying powder feeder and sprayed onto the surface of the C / C composite material with embedded SiC binder to prepare a Yb2Si2O7-Al2O3 ceramic surface layer. The spraying power is 46kW and the spraying distance is 100mm.
[0058] Step 6: Place the sprayed sample obtained in Step 5 in a high-temperature tubular heat treatment furnace, heat it to 1300℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 10h.
[0059] Step 7: After the above sample was oxidized at 1500℃ in an environment of 50 vol.% O2 + 50 vol.% H2O for 78 h, the mass increase was 0.43%.
[0060] Comparative Example 1:
[0061] Step 1: Yb2Si2O7 powder is loaded into a plasma spraying powder feeder and sprayed onto the surface of the C / C composite material with embedded SiC binder to prepare a Yb2Si2O7 ceramic surface layer. The spraying power is 46kW and the spraying distance is 100mm.
[0062] Step 2: Place the sprayed sample obtained in Step 1 in a high-temperature tubular heat treatment furnace, raise the temperature to 1300℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold for 10h.
[0063] Step 3: After the above sample was oxidized at 1500℃ in an environment of 50 vol.% O2 + 50 vol.% H2O for 78 h, the mass increase was 0.37%.
[0064] Example 2:
[0065] Step 1: Place NaCl and KCl powders separately in a high-temperature tube heat treatment furnace, raise the temperature to 250℃ at a heating rate of 5℃ / min under Ar atmosphere and hold for 4 hours, then let them cool naturally to room temperature to ensure that the NaCl and KCl powders are fully dried.
[0066] Step 2: Weigh Al and Yb2Si2O7 powder and NaCl and KCl powder obtained in Step 1 at a molar ratio of 0.2:1:0.6:0.6. Place the weighed powder in an alumina mortar and grind manually for 20 minutes to obtain a mixed powder.
[0067] Step 3: Place the mixed powder obtained in Step 2 in a high-temperature tubular heat treatment furnace, heat it to 900℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 6 hours. Place the high-temperature treated mixed powder in deionized water and ultrasonically clean it at 80℃ for 30 minutes. Then, let the mixed slurry stand and pour off the supernatant. Repeat the above cleaning operation 5 times to remove NaCl and KCl. Place the completely cleaned mixed slurry in a 100℃ oven for 10 hours to obtain fully dried Yb2Si2O7@Al core-shell powder.
[0068] Step 4: Place the Yb2Si2O7@Al core-shell powder obtained in Step 3 into a high-temperature box furnace, raise the temperature to 500℃ at a heating rate of 5℃ / min in air atmosphere and hold for 4h to obtain Yb2Si2O7@Al2O3 core-shell powder for spraying.
[0069] Step 5: The Yb2Si2O7@Al2O3 core-shell powder obtained in Step 4 is loaded into a plasma spraying powder feeder and sprayed onto the surface of the C / C composite material with embedded SiC binder to prepare a Yb2Si2O7-Al2O3 ceramic surface layer. The spraying power is 46kW and the spraying distance is 100mm.
[0070] Step 6: Place the sprayed sample obtained in Step 5 in a high-temperature tubular heat treatment furnace, raise the temperature to 1300℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold for 10h.
[0071] Step 7: After the above sample was oxidized at 1500℃ in an environment of 50 vol.% O2 + 50 vol.% H2O for 150 h, the mass increase was 0.38%.
[0072] Comparative Example 2:
[0073] Step 1: Yb2Si2O7 powder is loaded into a plasma spraying powder feeder and sprayed onto the surface of the C / C composite material with embedded SiC binder to prepare a Yb2Si2O7 ceramic surface layer. The spraying power is 46kW and the spraying distance is 100mm.
[0074] Step 2: Place the sprayed sample obtained in Step 1 in a high-temperature tubular heat treatment furnace, raise the temperature to 1300℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold for 10h.
[0075] Step 3: After the above sample was oxidized at 1500℃ in an environment of 50 vol.% O2 + 50 vol.% H2O for 150 h, the mass increase was 0.08%.
[0076] Example 3:
[0077] Step 1: Place NaCl and KCl powders separately in a high-temperature tube heat treatment furnace, raise the temperature to 250℃ at a heating rate of 5℃ / min under an Ar atmosphere and hold for 4 hours, then allow them to cool naturally to room temperature to ensure that the NaCl and KCl powders are fully dried.
[0078] Step 2: Weigh Al and Yb2Si2O7 powders and NaCl and KCl powders obtained in Step 1 at a molar ratio of 0.2:1:0.6:0.6. Place the weighed powders in an alumina mortar and grind them manually for 20 minutes to obtain a mixed powder.
[0079] Step 3: Place the mixed powder obtained in Step 2 in a high-temperature tubular heat treatment furnace, heat it to 900℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 6 hours. Place the high-temperature treated mixed powder in deionized water and ultrasonically clean it at 80℃ for 30 minutes. Then, let the mixed slurry stand and pour off the supernatant. Repeat the above cleaning operation 5 times to remove NaCl and KCl. Place the completely cleaned mixed slurry in a 100℃ oven for 10 hours to obtain fully dried Yb2Si2O7@Al core-shell powder.
[0080] Step 4: Place the Yb2Si2O7@Al core-shell powder obtained in Step 3 into a high-temperature box furnace, heat it to 500℃ at a heating rate of 5℃ / min in air atmosphere and hold it at that temperature for 4 hours to obtain Yb2Si2O7@Al2O3 core-shell powder for spraying.
[0081] Step 5: The Yb2Si2O7@Al2O3 core-shell powder obtained in Step 4 is loaded into a plasma spraying powder feeder and sprayed onto the surface of the C / C composite material with embedded SiC binder to prepare a Yb2Si2O7-Al2O3 ceramic surface layer. The spraying power is 46kW and the spraying distance is 100mm.
[0082] Step 6: Place the sprayed sample obtained in Step 5 in a high-temperature tubular heat treatment furnace, heat it to 1300℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 10h.
[0083] Step 7: After the above sample was oxidized at 1500℃ in an environment of 50 vol.% O2 + 50 vol.% H2O for 200 h, the mass increase was 0.48%.
[0084] Figure 3 The following is a cross-sectional backscattering morphology of the sample corresponding to Example 3 after oxidation in an environment of 1500℃, 50 vol.% O2 + 50 vol.% H2O for 200 h:
[0085] (a) Low-magnification morphology of the Yb2Si2O7-Al2O3 coating sample after water-oxygen corrosion; (b) Local magnified morphology of the reaction layer; (c) Local magnified morphology of the middle part of the Yb2Si2O7-Al2O3 surface layer; (d) Local magnified morphology of the thermally grown oxide (TGO) layer. It can be seen that after 200 hours of water-oxygen corrosion, due to the diffusion of Al elements to the coating surface, a relatively dense Yb3Al5O3 layer is formed on the surface of the Yb2Si2O7-Al2O3 coating sample. 12 Reaction layer. In addition, a significant amount of gray Yb3Al5O is dispersed within the Yb2Si2O7-Al2O3 surface layer. 12 It contains a dark gray aluminosilicate phase, and almost no residue of the spray decomposition product Yb2SiO5 is present.
[0086] Comparative Example 3:
[0087] Step 1: Yb2Si2O7 powder is loaded into a plasma spraying powder feeder and sprayed onto the surface of the C / C composite material with embedded SiC binder to prepare a Yb2Si2O7 ceramic surface layer. The spraying power is 46kW and the spraying distance is 100mm.
[0088] Step 2: Place the sprayed sample obtained in Step 1 in a high-temperature tubular heat treatment furnace, raise the temperature to 1300℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold for 10h.
[0089] Step 3: After the above sample was oxidized at 1500℃ in an environment of 50 vol.% O2 + 50 vol.% H2O for 200 h, the mass increase was 0.16%.
[0090] Figure 2 The XRD patterns of the samples corresponding to Example 3 and Comparative Example 3 after oxidation at 1500℃ in an environment of 50 vol.% O2 + 50 vol.% H2O for 200 h are shown. After 200 h of water-oxygen corrosion, the surface of the Yb2Si2O7-Al2O3 coated sample is mainly composed of Yb3Al5O 12 The phase composition was also analyzed, and small amounts of Yb2SiO5 and Yb2Si2O7 phases were also detected. The surface of the Yb2Si2O7 coated sample was mainly composed of Yb2SiO5 and a small amount of Yb2Si2O7 phase.
[0091] Figure 4 The cross-sectional backscattering morphology of the sample corresponding to Comparative Example 3 after oxidation in an environment of 1500℃, 50 vol.% O2 + 50 vol.% H2O for 200 h is shown below:
[0092] (a) Low-magnification morphology of the Yb₂Si₂O₇ coating sample after water-oxygen corrosion; (d) Local magnified morphology of the reaction layer; (c) Local magnified morphology of the middle part of the Yb₂Si₂O₇ surface layer; (d) Local magnified morphology of the thermally grown oxide layer. After 200 h of water-oxygen corrosion, a porous Yb₂SiO₅ reaction layer was formed on the surface of the Yb₂Si₂O₇ coating sample. Due to the nearly twice high coefficient of thermal expansion of Yb₂SiO₅ compared to Yb₂Si₂O₇, a large number of cracks were distributed in the Yb₂SiO₅ reaction layer. In addition, unlike the Yb₂Si₂O₇-Al₂O₃ surface layer, where Yb₂SiO₅ phase is almost no longer distributed, some Yb₂SiO₅ remains in the Yb₂Si₂O₇ surface layer. The presence of Yb₂SiO₅ with a high coefficient of thermal expansion causes more microcracks in the surface layer, which will weaken the thermal cycling stability of the coating.
[0093] Figure 5 The following data pertain to the mass changes and the thicknesses of the thermally grown oxide layer and reaction layer of the samples corresponding to Example 3 and Comparative Example 3 after oxidation at 1500°C in a 50 vol.% O2 + 50 vol.% H2O environment for 200 h:
[0094] (a) Mass changes of Yb₂Si₂O₇ and Yb₂Si₂O₇-Al₂O₃ coated samples after 200 hours of water-oxygen corrosion; (b) Statistical analysis of the thickness of the thermally grown oxide layer and reaction layer of Yb₂Si₂O₇ and Yb₂Si₂O₇-Al₂O₃ coated samples after 200 hours of water-oxygen corrosion. It can be seen that the Yb₂Si₂O₇ coated sample loses weight after 18 hours of water-oxygen corrosion, and the Yb₂Si₂O₇-Al₂O₃ coated sample gains approximately three times the weight of the pure Yb₂Si₂O₇ coated sample after 200 hours of corrosion. Furthermore, after 200 hours of corrosion, both groups of samples form thermally grown oxide layers of similar thickness, while the thickness of the porous Yb₂SiO₅ reaction layer formed on the surface of the Yb₂Si₂O₇ coated sample is approximately the same as the thickness of the Yb₂Si₂O₇-Al₂O₃ coated sample. 12 The reaction layer thickness is three times that of the sample. Analysis of the water-oxygen corrosion process revealed that the weight gain was mainly due to the thickening of the thermally grown oxide layer and contamination by the Al2O3 furnace tube, while the weight loss was primarily due to the erosion of the surface material by water vapor. Since both groups of samples were tested in the same environment, the contamination effect of the Al2O3 furnace tube on the samples was approximately the same. Therefore, for samples with similar thermally grown oxide layer thicknesses, their resistance to water vapor corrosion can be assessed by measuring the sample's mass loss. In conclusion, the Yb2Si2O7-Al2O3 coated sample exhibited superior performance in a 1500℃ water-oxygen corrosion environment.
[0095] Comparative Example 4:
[0096] Step 1: Place NaCl and KCl powders separately in a high-temperature tube heat treatment furnace, raise the temperature to 250℃ at a heating rate of 5℃ / min under Ar atmosphere and hold for 4 hours, then let them cool naturally to room temperature to ensure that the NaCl and KCl powders are fully dried.
[0097] Step 2: Weigh Al and Yb2Si2O7 powder and NaCl and KCl powder obtained in Step 1 at a molar ratio of 0.5:1:1.5:1.5. Place the weighed powder in an alumina mortar and grind manually for 20 minutes to obtain a mixed powder.
[0098] Step 3: Place the mixed powder obtained in Step 2 in a high-temperature tube heat treatment furnace, heat it to 900℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 6 hours. Place the high-temperature treated mixed powder in deionized water and ultrasonically clean it at 80℃ for 30 minutes. Then, let the mixed slurry stand and pour off the supernatant. Repeat the above cleaning operation 5 times to remove NaCl and KCl. Place the completely cleaned mixed slurry in a 100℃ oven for 10 hours to obtain fully dried Yb2Si2O7@Al core-shell powder.
[0099] Step 4: Place the Yb2Si2O7@Al core-shell powder obtained in Step 3 into a high-temperature box furnace, raise the temperature to 500℃ at a heating rate of 5℃ / min in air atmosphere and hold for 6h to obtain Yb2Si2O7@Al2O3 core-shell powder for spraying.
[0100] Step 5: The Yb2Si2O7@Al2O3 core-shell powder obtained in Step 4 is loaded into a plasma spraying powder feeder and sprayed onto the surface of the C / C composite material with embedded SiC binder to prepare a Yb2Si2O7-Al2O3 ceramic surface layer. The spraying power is 48kW and the spraying distance is 100mm.
[0101] Step 6: After the above sample was oxidized in an environment of 1500℃ and 50 vol.% O2 + 50 vol.% H2O for 20 h, the coating showed blistering. It can be seen from this comparative example that the coating blistering was caused by the proportion of salt added during the preparation process exceeding the designed content.
[0102] Example 4
[0103] Step 1: Place NaCl and KCl powders separately in a high-temperature tube heat treatment furnace, raise the temperature to 200℃ at a rate of 5℃ / min under an Ar atmosphere and hold for 6 hours, then allow them to cool naturally to room temperature to ensure that the NaCl and KCl powders are fully dried.
[0104] Step 2: Weigh Al and Yb2Si2O7 powders and NaCl and KCl powders obtained in Step 1 at a molar ratio of 0.1:1:0.3:0.3. Place the weighed powders in an alumina mortar and grind them manually for 20 minutes to obtain a mixed powder.
[0105] Step 3: Place the mixed powder obtained in Step 2 in a high-temperature tubular heat treatment furnace, heat it to 700℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 6 hours. Place the high-temperature treated mixed powder in deionized water and ultrasonically clean it at 80℃ for 30 minutes. Then, let the mixed slurry stand and pour off the supernatant. Repeat the above cleaning operation 5 times to remove NaCl and KCl. Place the completely cleaned mixed slurry in a 100℃ oven for 10 hours to obtain fully dried Yb2Si2O7@Al core-shell powder.
[0106] Step 4: Place the Yb2Si2O7@Al core-shell powder obtained in Step 3 into a high-temperature box furnace, heat it to 500℃ at a heating rate of 5℃ / min in air atmosphere and hold it at that temperature for 4 hours to obtain Yb2Si2O7@Al2O3 core-shell powder for spraying.
[0107] Step 5: The Yb2Si2O7@Al2O3 core-shell powder obtained in Step 4 is loaded into a plasma spraying powder feeder and sprayed onto the surface of the C / C composite material with embedded SiC binder to prepare a Yb2Si2O7-Al2O3 ceramic surface layer. The spraying power is 45kW and the spraying distance is 120mm.
[0108] Step 6: Place the sprayed sample obtained in Step 5 in a high-temperature tubular heat treatment furnace, heat it to 1100℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 15h.
[0109] Example 5
[0110] Step 1: Place NaCl and KCl powders separately in a high-temperature tube heat treatment furnace, raise the temperature to 220℃ at a heating rate of 5℃ / min under an Ar atmosphere and hold for 5 hours, then allow them to cool naturally to room temperature to ensure that the NaCl and KCl powders are fully dried.
[0111] Step 2: Weigh Al and Yb2Si2O7 powders and NaCl and KCl powders obtained in Step 1 at a molar ratio of 0.1:1:0.4:0.4. Place the weighed powders in an alumina mortar and grind them manually for 20 minutes to obtain a mixed powder.
[0112] Step 3: Place the mixed powder obtained in Step 2 in a high-temperature tubular heat treatment furnace, heat it to 800℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 5 hours. Place the high-temperature treated mixed powder in deionized water and ultrasonically clean it at 80℃ for 30 minutes. Then, let the mixed slurry stand and pour off the supernatant. Repeat the above cleaning operation 5 times to remove NaCl and KCl. Place the completely cleaned mixed slurry in a 100℃ oven for 10 hours to obtain fully dried Yb2Si2O7@Al core-shell powder.
[0113] Step 4: Place the Yb2Si2O7@Al core-shell powder obtained in Step 3 into a high-temperature box furnace, heat it to 500℃ at a heating rate of 5℃ / min in air atmosphere and hold it at that temperature for 5h to obtain Yb2Si2O7@Al2O3 core-shell powder for spraying.
[0114] Step 5: The Yb2Si2O7@Al2O3 core-shell powder obtained in Step 4 is loaded into a plasma spraying powder feeder, and a Yb2Si2O7-Al2O3 ceramic surface layer is prepared by spraying onto the surface of the C / C composite material with embedded SiC binder. The spraying power is 50kW and the spraying distance is 80mm.
[0115] Step 6: Place the sprayed sample obtained in Step 5 in a high-temperature tubular heat treatment furnace, heat it to 1200℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 10h.
[0116] Example 6
[0117] Step 1: Place NaCl and KCl powders separately in a high-temperature tube heat treatment furnace, raise the temperature to 230℃ at a heating rate of 5℃ / min under an Ar atmosphere and hold for 5 hours, then allow them to cool naturally to room temperature to ensure that the NaCl and KCl powders are fully dried.
[0118] Step 2: Weigh Al and Yb2Si2O7 powders and NaCl and KCl powders obtained in Step 1 at a molar ratio of 0.3:1:0.7:0.7. Place the weighed powders in an alumina mortar and grind them manually for 20 minutes to obtain a mixed powder.
[0119] Step 3: Place the mixed powder obtained in Step 2 in a high-temperature tubular heat treatment furnace, heat it to 1000℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 4 hours. Place the high-temperature treated mixed powder in deionized water and ultrasonically clean it at 80℃ for 30 minutes. Then, let the mixed slurry stand and pour off the supernatant. Repeat the above cleaning operation 5 times to remove NaCl and KCl. Place the completely cleaned mixed slurry in a 100℃ oven for 10 hours to obtain fully dried Yb2Si2O7@Al core-shell powder.
[0120] Step 4: Place the Yb2Si2O7@Al core-shell powder obtained in Step 3 into a high-temperature box furnace, heat it to 500℃ at a heating rate of 5℃ / min in air atmosphere and hold it at that temperature for 5h to obtain Yb2Si2O7@Al2O3 core-shell powder for spraying.
[0121] Step 5: The Yb2Si2O7@Al2O3 core-shell powder obtained in Step 4 is loaded into a plasma spraying powder feeder and sprayed onto the surface of the C / C composite material with embedded SiC binder to prepare a Yb2Si2O7-Al2O3 ceramic surface layer. The spraying power is 48kW and the spraying distance is 110mm.
[0122] Step 6: Place the sprayed sample obtained in Step 5 in a high-temperature tubular heat treatment furnace, heat it to 1100℃ at a heating rate of 5℃ / min under Ar atmosphere, and hold it at that temperature for 12h.
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an environmental barrier coating for C / C composite materials, characterized in that, Includes the following steps: Step 1: Mix Al powder, Yb2Si2O7 powder, NaCl powder and KCl powder, and grind them to obtain a mixed powder; the molar ratio of Al powder, Yb2Si2O7 powder, NaCl powder and KCl powder is (0.1~0.3):1:(0.3~0.7):(0.3~0.7). Step 2: Heat and hold the mixed powder in a heating furnace to obtain the heat-treated mixed powder; the holding temperature is 700~1000℃, the holding environment is Ar atmosphere, and the holding time is 4~6h. Step 3: Perform ultrasonic cleaning on the heat-treated mixed powder several times, and dry the final ultrasonically cleaned slurry to obtain Yb2Si2O7@Al core-shell powder. Step 4: Oxidize the Yb2Si2O7@Al core-shell powder to obtain Yb2Si2O7@Al2O3 core-shell powder; in the Yb2Si2O7@Al2O3 core-shell powder, the core is Yb2Si2O7 and the shell is Al2O3, and the thickness of the shell is less than 1μm; the oxidation temperature is 500℃ and the oxidation time is 4~6h; Step 5: Deposit Yb2Si2O7-Al2O3 core-shell powder on the surface of the C / C composite material with embedded SiC binder layer to obtain Yb2Si2O7-Al2O3 ceramic surface layer; Step 6: The C / C composite material with Yb2Si2O7-Al2O3 ceramic surface layer deposited on the surface is heat-treated in a heating furnace to obtain an environmental barrier coating for C / C composite material. During high-temperature service, the Yb2Si2O7-Al2O3 ceramic surface layer undergoes an in-situ reaction to generate Yb3Al5O3. 12 During high-temperature service, the SiO2 displaced by the in-situ reaction is further sprayed to produce low-Yb2SiO5, which is then converted into Yb2Si2O7.
2. The method for preparing an environmental barrier coating for C / C composite materials according to claim 1, characterized in that, In step 1, the NaCl powder and KCl powder are dried.
3. The method for preparing an environmental barrier coating for C / C composite materials according to claim 1, characterized in that, In step 3, the ultrasonic cleaning is performed 5 times, and the liquid temperature used in the ultrasonic cleaning is 80℃.
4. The method for preparing an environmental barrier coating for C / C composite materials according to claim 1, characterized in that, In step 3, the slurry drying temperature is 100℃ and the drying time is 10h.
5. The method for preparing an environmental barrier coating for C / C composite materials according to claim 1, characterized in that, In step 5, Yb2Si2O7-Al2O3 core-shell powder is deposited by plasma spraying process, with a spraying power of 45~50kW and a spraying distance of 80~120mm.
6. The method for preparing an environmental barrier coating for C / C composite materials according to claim 1, characterized in that, In step 6, the heat preservation temperature is 1100~1300℃, the heat preservation atmosphere is Ar atmosphere, and the heat preservation time is 10~15h.
7. An environmental barrier coating for C / C composite materials obtained by the preparation method according to any one of claims 1-6, characterized in that, The environmental barrier coating consists of a SiC bonding layer and a Yb2Si2O7-Al2O3 ceramic surface layer from the inside out.
Citation Information
Patent Citations
Preparation method of thermal protective ceramic powder
CN106342082B
Silica-rich barrier coatings
US20210221749A1